Amorphous silicon and silicates-stabilized ZrO2 hollow fiber with low thermal conductivity and high phase stability derived from a cogon template. Issue 6 (15th April 2019) - Wang, Tianchi; Zhang, Zihao; Dai, Changhao; Li, Qi; Li, Yicong; Kong, Jian; Wong, Chingping
Abstract: ZrO2 fibers are used as refractory materials owing to their excellent thermal resistance and thermal stability. Natural cogon fiber is a type of hollow Gramineae fiber, and usually contains a small amount of amorphous silicon and silicates, such as SiO2, MgSiO3, CaSiO4, and Al2 SiO5, which can effectively avoid the phase transition of ZrO2 . In this study, hollow ZrO2 fibers with remarkable thermal insulation and phase stability were synthesized using a cogon fiber template. The results showed that the final ZrO2 fibers successfully inherited the hollow structure and amorphous substance from the cogon template. The hollow structure of the biomorphic ZrO2 fiber helped prevent heat flow more efficiently compared to solid fibers and reduced the thermal conductivity to a significant extent. In addition, the amorphous silicon and silicates played an important role in the phase stability of tetragonal ZrO2 ; the transformation from the tetragonal to monoclinic phase was avoided at room temperature and in humid environment.